(untitled) (International journal of artificial intelligence, 2026)
This study is devoted to the analysis of the complex and multifaceted relationship between dialects and the literary language in the history of the Uzbek language based on a historical-linguistic approach. The study considers dialects as an important source in the formation and development of the Uzbek literary language, and the influence of their phonetic, lexical and grammatical features on the norms of the literary language is consistently highlighted. The work provides a comparative analysis of written sources of the ancient Turkic period, samples of the old Uzbek literary language and modern dialect materials, paying special attention to the issues of historical continuity and coherence. Also, the role of regional dialects in the formation of literary language norms, the processes of their selection and assimilation into the national language are studied in connection with sociolinguistic factors. The results of the study show that the interaction between dialects and the literary language is not a one-sided, but a dynamic and complex process. This scientific work serves as a theoretical and practical basis for a deeper understanding of the laws of the historical development of the Uzbek language, as well as for improving literary language norms and the effective use of dialect materials.